(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article provides insights into the use of the heritage of Eastern scholars in preparing students for family life, ensuring the development of their personal and professional qualities. It discusses the continuous improvement of utilizing the legacy of Eastern scholars in the process of studying general pedagogy.